Contemporary uses of old folks: the immunomodulatory and toxic potential of fenbufen - Akhtar, Muhammad Furqan; Nisa, Mehr-un-; Saleem, Ammara; Hamid, Irfan; Alsharif, Khalaf F.; Abdel-Daim, Mohamed M.; Rahman, Md. Habibur; Shah, Muddaser; Sohail, Kashif; Javaid, Zeeshan (Cellular and Molecular Biology, 2022)
Fenbfen is used for pain, pyrexia and in the management of osteoarthritis, rheumatoid arthritis and other musculoskeletal disorders. The present research was planned to examine the immunomodulatory activity of fenbufen in different models of cell-mediated immunity (CMI) and humoral immunity (HI). The CMI was evaluated by delayed-type hypersensitivity (DTH) and cyclophosphamide-induced neutropenia assays while HI was appraised by hemagglutination (HA) assay by administering fenbufen at 2, 6 and 10 mg.kg-1 and azathioprine 40 mg.kg-1 (as standard therapy) to albino mice by intraperitoneal route. The ex vivo immunomodulatory action was determined by red blood cell (RBC) membrane stabilization and protein denaturation assays. The results showed that fenbufen treatment had significantly (p<0.05-p<0.001) reduced white blood cells, hemoglobin content, and red blood cells in the healthy and neutropenic mice. A significant (p<0.001) reduction in activities of superoxide dismutase and catalase and glutathione contents, and enhancement of malondialdehyde level were observed in neutropenic mice that were restored by fenbufen treatment. It suppressed DTH reaction after 24, 48 and 72 h post topical application of 2, 4-dinitrofluorobenzene (DNFB). Fenbufen or azathioprine treated groups also showed a significant reduction in the antibody titer against human RBCs induced immune activation in mice as compared to the disease control mice. Fenbufen showed IC50 of 14.0, 50.5 and 66.2 μg.ml-1 whereas, diclofenac sodium showed IC50 of 61.0, 126 and 50.5 μg/ml in RBCs membrane stabilization, egg albumin and bovine serum albumin denaturation assays respectively. The current study shows that fenbufen might have potential immunomodulatory activity against CMI and HI. It can be utilized to treat immune system disorders.